Inhibition of caspase-1 prolongs survival of mice infected with rabies virus. Issue 33 (2nd August 2019) - Koraka, Penelope; Martina, Byron E.E.; Smreczak, Marcin; Orlowska, Anna; Marzec, Anna; Trebas, Pawel; Roose, Jouke M.; Begeman, Lineke; Gerhauser, Ingo; Wohlsein, Peter; Baumgärtner, Wolfgang; Zmudzinski, Jan; et al.
Abstract: Rabies virus infects almost all mammals resulting in lethal disease. To date there is no treatment available for symptomatic rabies and there is an urgent need to develop treatment strategies that would prolong survival, thereby providing a window of opportunity for the host to mount a protective immune response. We hypothesized that both virus and excessive immune response contribute to disease and that interfering with both is necessary to prevent lethal disease. Here, we have inhibited the pro-inflammatory response associated with pyroptosis and showed that inhibition of CASP-1 had a beneficial effect on survival time. Our results confirm that some inflammatory responses may be involved in the pathogenesis of severe disease and the results suggest that effective intervention includes inhibition of virus and host response.